2020
DOI: 10.1002/adma.202002054
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Macrophages for Cancer Immunotherapy and Drug Delivery

Abstract: was that most nanoparticles do not have a sufficiently long blood half-life and cannot realize deep penetration in tumor tissue. Thus, recent progress in the development of strategies for mimicking or modulating cells offers a highly attractive alternative to drug delivery. [10-17] As natural immune cells and antigenpresenting cells, macrophages [18] have a long blood half-life and can specifically bind to tumor tissue. Therefore, applying macrophages in chemical drug delivery would lead to a significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
484
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 628 publications
(493 citation statements)
references
References 170 publications
(198 reference statements)
9
484
0
Order By: Relevance
“…Recent studies have demonstrated that the tumor microenvironment (TME) plays the key role influencing the efficacy of anti-tumor immunotherapy, in which tumor-associated macrophages (TAMs) are the most important component ( Bohn et al, 2018 ; Xia et al, 2020 ). TAMs are abundant in multiple cancers compared to adjacent tissues, supporting oncogenesis, vascularization in spite of immunosurveillance ( Yang and Zhang, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the tumor microenvironment (TME) plays the key role influencing the efficacy of anti-tumor immunotherapy, in which tumor-associated macrophages (TAMs) are the most important component ( Bohn et al, 2018 ; Xia et al, 2020 ). TAMs are abundant in multiple cancers compared to adjacent tissues, supporting oncogenesis, vascularization in spite of immunosurveillance ( Yang and Zhang, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…loading macrophage membrane surfaces with nanoparticles can be carried out by extrusion or in an ultrasonic bath. Macrophage membrane coatings have been critical in prolonging the circulation time of nano-drug delivery systems in vivo, further enhancing the efficiency of drug delivery and therapeutic efficacy (Tong et al, 2016;Zhang et al, 2018;Xia et al, 2020). Therefore, the macrophage-based nanosystems exhibit great potential for controlled drug delivery in periodontitis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the overview of the tumor microenvironment (TME) may help find new ways to treat HNSCC or change TME to improve the effectiveness of immunotherapy. Macrophages that reside within the TME are known as tumor-associated macrophages (TAMs) ( 52 ). TAMs and other TME members make up the tumor ecosystem.…”
Section: Discussionmentioning
confidence: 99%